Hybrid energy storage system for dynamic power management in grid-connected microgrid - Kamagaté, Yaya; Shah, Heli Amit (Institute of Advanced Engineering and Science, 2025)
This paper presents an adaptive rule-based approach for dynamic power management in grid-connected microgrids. Solar photovoltaics (PV) and a battery-ultracapacitor hybrid energy storage system form the DC subsystem. Initially, the reference power is processed through a low-pass filter, diverting high-frequency power variations to the ultracapacitor, thereby safeguarding the battery. Then, a power allocation factor proportional to the battery state of charge manages the average power distribution between the battery and the grid. Finally, a microgrid power management system (MPMS) establishes rules to regulate power sharing among sources and loads. In the proposed method, the battery handles long-term energy requirements, the ultracapacitor meets short-term power demands, and the grid is adjusted to align with the system’s requirements. The main benefits involve effective power distribution among sources and loads, DC bus voltage stabilization, smooth transitions between different operating modes, and enhanced grid power quality. Additionally, safety protocols prevent overcharging/deep discharging, thus reducing the risk of premature degradation and resulting in longer lifespan of storage devices. MATLAB/Simulink is used to implement and validate the method.